Cementless total hip arthroplasty in patients with ankylosing spondylitis: A retrospective observational study - Xu, Jun (Medicine (Baltimore), 2017)
Controversies on the surgical protocols and efficacies of total hip arthroplasty (THA) in ankylosing spondylitis (AS) still exist. The aim of this study was to retrospectively analyze the perioperative managements and their outcomes related to performing THA on patients with AS. Data of 54 AS patients who underwent 81 THAs between 2008 and 2014 were retrospectively analyzed. Clinical and imaging data were collected preoperatively, postoperatively, and during the follow-up period for surgical efficacy. Using posterolateral approach, cementless prostheses were selected in all cases. Mean follow-up period was 3.6 years (range, 2–8 years). Inclinations and anteversions of acetabular cups were 36.3°±4.5° (range, 30°–50°) and 12.3°±4.9° (range, 0°–25°) respectively. Mean visual analog scale (VAS) score decreased from 6.7 ± 2.1 (range, 4–10) preoperatively to 1.5 ± 1.0 (range, 0–4) at final follow-up, and mean Harris hip score (HHS) improved from 31.2 ± 11.6 (range, 15–45) to 86.1 ± 4.3 (range, 80–95) (P < 0.05). Postoperative range of motion (ROM) in flexion was improved from 6.7°±13.5° (range, 0°–50°) preoperatively to 82.5°±6.4° (range, 70°–100°) at final follow-up, and ROM in extension was improved from 1.8°±5.7°(range, 0°–15°) to 15.4°±2.6° (range, 10°–20°) (P < 0.05). Heterotopic ossification (HO) was documented in 9 hips (11.1%). Signs of stable fibrous ingrowth and bone ingrowth were detected in 52 and 29 hips, respectively. Sciatic never injury was occurred in 3 cases, and treated conservatively. There were no signs of periprosthetic fractures, dislocation, or prosthesis loosening. Surgical efficacies of THA for AS patients with severe hip involvement are satisfactory.